2022
DOI: 10.1096/fj.202201079rr
|View full text |Cite
|
Sign up to set email alerts
|

Graphene oxide accelerates diabetic wound repair by inhibiting apoptosis of Ad‐MSCs via Linc00324/miR‐7977/STK4 pathway

Abstract: Many studies have shown that graphene oxide (GO) promotes proliferation and differentiation of a variety of stem cells. However, its effect on adipose‐derived mesenchymal stem cell (Ad‐MSCs) apoptosis is still unclear. Apoptosis is a significant factor affecting stem cell‐based treatment of diabetic wounds. Therefore, we explored the effect of GO on Ad‐MSC apoptosis and diabetic wound healing. In this study, qRT‐PCR was used to detect Ad‐MSC expression of LncRNAs, miRNAs, and mRNAs under high‐glucose environme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…As for tripartite motif containing 56 ( TRIM56 ), previous studies have shown that it plays a crucial role in regulating immune response and viral defense by promoting the activation of innate immunity and inducing expression of interferon-stimulated genes [ 74 , 75 ]. Moreover, serine/threonine kinase 4 ( STK4 ) has been reported to be involved in regulating apoptosis and cell proliferation [ 76 , 77 ]. Excision repair cross-complementation group 2 ( ERCC2 ) is engaged in nucleotide excision repair, a crucial DNA repair pathway that protects DNA against the harmful effects of UV radiation and other DNA-damaging agents [ 78 , 79 ].…”
Section: Discussionmentioning
confidence: 99%
“…As for tripartite motif containing 56 ( TRIM56 ), previous studies have shown that it plays a crucial role in regulating immune response and viral defense by promoting the activation of innate immunity and inducing expression of interferon-stimulated genes [ 74 , 75 ]. Moreover, serine/threonine kinase 4 ( STK4 ) has been reported to be involved in regulating apoptosis and cell proliferation [ 76 , 77 ]. Excision repair cross-complementation group 2 ( ERCC2 ) is engaged in nucleotide excision repair, a crucial DNA repair pathway that protects DNA against the harmful effects of UV radiation and other DNA-damaging agents [ 78 , 79 ].…”
Section: Discussionmentioning
confidence: 99%
“…The expression of STK4 promoted circRNA_0057209 by sponging miR-183, thereby enhancing YAP phosphorylation, activating the Hippo pathway, and inhibiting tumor progression[16]. It is worth noting that a previous study showed that miR-7977 signi cantly reduced the expression of the Hippo core kinase STK4, inhibited the Hippo-YAP signaling pathway, and affected the development of acute myeloid leukemia[17]. Interestingly, apoptosis of adipose-…”
mentioning
confidence: 99%